Correction: Enhanced actuated strain of titanium dioxide/nitrile-butadiene rubber composite by the biomimetic method. Issue 86 (18th September 2015) - Yang, Dan; Huang, Shuo; Wu, Yibo; Ruan, Mengnan; Li, Shuxin; Shang, Yuwei; Cui, Xiuguo; Wang, Yang; Guo, Wenli
<x xml:space="preserve">Abstract</x> Correction for 'Enhanced actuated strain of titanium dioxide/nitrile-butadiene rubber composite by the biomimetic method' by Dan Yang et al., RSC Adv., 2015, 5, 65385–65394.